The Effect of A Proposed Training Program In volleyball On Some Physiological and Skill Variables - Azab, Mahmoud (Journal of Physical Education, 2017)
The Effect of A Proposed Training Program In volleyball On Some Physiological and Skill Variables The study aimed to know the effect of the proposed training program in volleyball on some physiological variables and skill,.The study was conducted on 16-09- 2016 until 14-12-2016 on a sample of 22 students from the specialization of Physical Education in Palestine Technical University - Khadouri students. After statistical analysis of appropriate data study researcher concluded that there are significant differences in each of the weight measurement and the percentage of grease and some volleyball skills (transmitter accuracy, and scroll up and scroll down, and on this it was concluded the researcher set of recommendations including the need to take advantage of the proposed training program to change the weight and the proportion of grease.The need to take advantage of the proposed training program to make a positive change in some skills for volleyball (serving ,forearm passing , overhead passing